The Strategic Selection of a Telemedicine Platform: A Guide for Digital Health Professionals - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2025)
The rapid ascent of telemedicine and digital health has fundamentally reshaped healthcare delivery. With the global telehealth market projected to expand at ...
Keywords: Digital Health; Artificial Intelligence; Healthcare Innovation; Medical Ethics; Patient Care